Health Literacy Associated with Sexual Risk Behavior of Sexually Transmitted Infections Among Adolescents - Sutheeraphrasert, Praewathip; Wirunpan, Bosaporn; Chaisingh, Rhatha (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: The morbidity rate of sexually transmitted infections (STIs) among adolescents tends to increase steadily. The main problem is that adolescents also engage in sexually unsafe risky behaviors. According to past studies, there have been a lot of studies on sexual risk behaviors in adolescents. However, there have been no definitive studies about the association between various factors and health literacy with the sexual risk behavior of STIs in adolescents, which is still controversial. This study aims to evaluate the association between health literacy and sexual risk behavior of sexually transmitted infections among adolescents. Method: A cross-sectional analytical study was conducted among a population of Thai adolescents aged 15-24 years who were in an educational institution in Muang District, Ubon Ratchathani Province in 2023. The primary outcome of this study was the sexual risk behavior in STIs of adolescents and factors of interest such as health literacy. Questionnaires were administered for data collection. Statistical analysis includes descriptive statistics for the characteristics data were described using frequency and percentage for categorical data. The mean, standard deviation, median, and minimum and maximum ranges were used for continuous data. Both bivariate and multiple logistic regression to evaluate the association between each factor and sexual risk behavior in STIs. Results were presented as adjusted odds ratio with 95% confidence interval and p-value was computed to determine the level of significance. Result: of 450 adolescents aged 15-24 years, 47.56% were female and 52.44% were male, with a mean age of 19.07± 2.37 years old (range: 15-24). The overall percentage of high levels of sexual risk behaviors for STIs was 77.33%. Adolescents with low sexual health literacy were found to have a high level of sexual risk behaviors for STIs of 78.81% and male adolescents were found in 74.15%. Low sexual health literacy and male adolescents were more likely to have a high level of sexual risk behaviors for STIs (ORadj= 1.09; 95% CI: 0.29 – 1.17 and ORadj= 5.10; 95% CI:1.98 – 5.08, respectively). Conclusion: Our findings demonstrated a high percentage of high levels of sexual risk behaviors for STIs among adolescents. Adolescents who had a low health literacy were more likely to have a high level of sexual risk behavior for STIs. Comprehensive sexually transmitted infection (STIs) prevention programs should be implemented, especially for adolescents.